The Impact of The Accounting Information System on The Relationship between The Application of Fair Value Accounting and The Characteristics of Accounting Information. - Emad Harash Essam; Fatima Jasime Mohammed; Suhail Al-Timimi (Journal of Madenat Alelem University College, 2020)
The study aims to study the effect of the accounting information system on the relationship between the application of fair value accounting and the characteristics of accounting information (Relevance, Representation, and Comparability) produced by the system and included in the financial statements for the listed companies in the Iraqi Stock Exchange. The finding of study indicated the important role that (IFRS9) and the accounting information system play in achieving high levels of appropriateness.